مقوّمات النّصرة والتّمكين للأمّة الإسّلامية من خلال السّنة - دراسة موضوعية - - دقعة صفاء (University of Eloued جامعة الوادي, 2024)
إن هذه الدراسة تهدف إلى معرفة اهتمام السنَّة النبوية بموضوع النصرة والتمكين، حيث أبرزت بمباحثها الثلاث مدى أهمية النصرة والتمكين للأمة الإسلامية، وكيف أن النَّبي – صلى الله عليه وسلم – نبَّه عليها سواء بالأفعال أو الأقوال، كما تناولت الدراسة بيان مقومات النصرة والتمكين من خلال السنَّة النبوية، وكذا نبهت بدراسة عوامل ضعف الأمة الإسلامية، وأن تخلي على أي مقوم في النُّصرة يؤدي إلى وهن الأمة، وتوِّجت الدراسة بعدد من التوصيات أهمها ضرورة إتباع منهج رباني بين أفراد الأمة الإسلامية، وكذلك الاقتداء بهدي النبي صلى الله عليه وسلم في إرساء مقومات النصرة والتمكين في المجتمع الإسلامي.This study is aimed at learning the interest of Sunnah in the subject of victory and empowerment. The three discussions highlighted the importance of victory and empowerment of the Islamic nation and how the Prophet Mohamed warned it whether it was by actions or money. The study also examined the elements of victory and empowerment through Sunnah. It also warned that the factors of the vulnerability of the Islamic nation and the abandonment of a figure in Al-Nusra would lead to the vulnerability of the nation. The study culminated in a number of recommendations, the most important of which were the adoption of the divine approach among the members of the Islamic nation Likewise, following the guidance of the Prophet Mohamed to establish the foundations of victory and empowerment in Islamic society.
Keywords: مقومات ، النصرة ، التمكين، السنة النبوية ..; components; victory; empowerment; the Sunnah of the Prophet.